Legitimation Strategies as Valuable Signals in Nonfinancial Reporting? Effects on Investor Decision-Making. Issue 4 (April 2021) - Hahn, Rüdiger; Reimsbach, Daniel; Kotzian, Peter; Feder, Madeleine; Weißenberger, Barbara E.
Companies disclosing negative aspects in sustainability reports often employ legitimation strategies to present mishaps in a favorable light. In incentivized experiments, we find that nonprofessional investors divest from companies with a negative sustainability-related incident, and that symbolic legitimation (which only evasively explains a negative incident) is not a strong enough signal to counter this divestment behavior. Even substantial legitimation (which reports on measures and behavioral change) mitigates the divestment decisions only if the company reports on concrete remediation actions in morally charged situations, such as social or environmental incidents. We elaborate these results in light of signaling and screening theory, and suggest the conceptual extension of "costly signals" to what we call "valuable signals." We argue that valuable signals need be not only costly for the sender from an economic perspective but also perceived as appropriate by the receiver from a noneconomic perspective.